Functional domains of the pp60v-src protein as revealed by analysis of temperature-sensitive Rous sarcoma virus mutants. - Stoker, A W (1984)
Four temperature-sensitive (ts) Rous sarcoma virus src gene mutants with lesions in different parts of the gene represent three classes of alteration in pp60src. These classes are composed of mutants with (i) heat-labile protein kinase activities both in vitro and in vivo (tsLA27 and tsLA29), (ii) heat-labile kinases in vivo but not in vitro (tsLA33), and (iii) neither in vivo nor in vitro heat-labile kinases (tsLA32). The latter class indicates the existence of structural or functional pp60src domains that are required for transformation but do not grossly affect tyrosine kinase activity.